Strategi Pembelajaran Matematika Berbasis Games Wordwall di Sekolah Dasar - Nufus, Ama; Damayanti, Rika; Enggar, Sri; Fitria, Siti; Adriansah, Toni (Universitas PGRI Palembang, 2025)
In the current era of digital learning, teachers must take a more active role in teaching their students. They also need to help students solve problems and use technology actively and consciously. By implementing this learning approach, teachers can enhance information, learning, innovation, media, and technology skills. The focus of this study will be towards the efficacy of learning using wordwalls strategy applied in the learning context, with the aim of identifying how this strategy can contribute to the improvement of students' abilities. It is anticipated that this study will offer insightful information to educators and policymakers in designing more effective and responsive learning practices to meet students' needs. The literature study method is used in this investigation. In order to boost students' interest in learning, the literature study for this study consists of a number of activities pertaining to gathering information from literature, reading and taking notes, and managing research data about the Wordwall Game-Based Mathematics Learning Strategy in Elementary Schools in a methodical, objective, analytical, and critical manner. The preparation of this literature review is identical to that of other studies. Reading, noting, and analyzing research materials from papers pertaining to this research variable are the distinct sources and methods of data collection.